PEMANFAATAN WINDOWS MOVIE MAKER SEBAGAI MEDIA PEMBELAJARAN BERBASIS AUDIO-VISUAL PADA MATA PELAJARAN SEJARAH DI SMAN 4 PALANGKA RAYA - Susanto, Yudi; Sumiatie, Sumiatie (Meretas: Jurnal Ilmu Pendidikan; Vol 5 No 1 (2018): Jurnal Ilmu Pendidikan Meretas, 2018)
The purpose of this research is to know how the utilization of Windows Movie Maker as audio-visual learning media on history subjects in SMA N 4 Palangka Raya first semester of the school year 2017-2018. This research used Research and Development method. The utilization result of Windows Movie Maker as audio-visual learning media has two important point that should be noticed, first is the visualization and second the duration. Researcher added more pictures & slide effect to make the media look alive, and to make the history learning process effective, at least 20 minutes duration used on every audio-visual media that made. The learning process will not achieve optimal results if it is not matched by the diversity of approaches and methods, both approaches individual, group, or classical. Based on the experiment result, it could be conclude that utilizing windows movie maker as audio-video learning media is suitable to use and able to increase the learning outcomes.